Penggunaan Media Flashcard Untuk Meningkatkan Pengenalan Bentuk Huruf Siswa Kelas II Pada Mata Pelajaran Bahasa Indonesia di SD Inpres Malakaya Kabupaten Gowa - Binti Rohmatin; Tasrif Akib; Muhammad Saeful (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan bahasa dan Sastra, 2023)
The main problem in this study is whether the use of flashcard media can improve letter recognition for second grade students in the Indonesian language subject at SD Inpres Malakaya, Gowa Regency. Based on the observations, several problems were found which were identified as the cause of the low recognition of letter shapes in class II students, namely the teacher still used one learning method and used less interesting media, so that learning became boring. This study aims to determine the use of flashcard media to improve letter recognition for class II students in the Indonesian language subject at SD Inpres Malakaya, Gowa Regency.This research uses Classroom Action Research (CAR) with individual learning models. CAR is carried out in two cycles where each cycle is held in three meetings with one evaluation. The subjects in this study were 25 grade II students of SD Inpres Malakaya, 15 male students and 10 female students.The data source is class II students, amounting to 25 students. CAR carried out in cycles I and II. The use of flashcard media in Indonesian subjects is proven to be able to improve the recognition of letter shapes for class II students. This can be seen from the results of the percentage of student completeness in cycle I by 24% and increased in cycle II by 92%. So it can be concluded that the use of flashcard media can improve the recognition of letter shapes for class II students of SD Inpres Malakaya, Gowa Regency.